Development and validation of a multiplex electrochemiluminescence immunoassay to evaluate dry eye disease in rat tear fluids - Agnese Compagnone; An Matheeussen; Linda De Vooght; Paul Cos (Scientific Reports, 2023)
Abstract Dry eye disease (DED) is a challenge in ophthalmology. Rat models represent valuable tools to study the pathophysiology and to develop novel treatments. A major challenge in DED research is detecting multiple biomarkers in a low tear volume sample. Multiplex immunoassays for DED rat research are missing. We have developed a multiplex electrochemiluminescence immunoassay (ECLIA) to detect three biomarkers for DED: MMP-9, IL-17 and ICAM-1. Tears, used as matrix, were collected from six healthy Wistar rats. Assays were run based on the U-Plex Meso Scale Diagnostics (MSD) platform, by two independent operators according to the EMA guideline on bioanalytical method validation. Linear mixed, regression models were fit to perform the statistical analysis on the range of concentrations for the chosen analytes. During optimization, it has observed that incubation time, temperature and agitation affected the robustness of the protocol. ECLIA optimum conditions include the use of antibodies at 0.5 µg/ml concentration and 1 h incubation at room temperature with shaking. Precision met the acceptance criteria in the chosen range: 1062–133 pg/ml for ICAM-1, 275–34.4 pg/ml for IL-17, 1750–219 pg/ml for MMP-9. Accuracy and linearity were acceptable for a broader range. This is the first report of a validated ECLIA that allows measurements of three relevant DED biomarkers in rat tear fluids.